Impact of Azadirachta indica Fruit Mucilage on particle size and swelling index in Central Composite Designed Acyclovir mucoadhesive microspheres (Baghdad Science Journal, 2023)
The drive of this exploration is to investigate the mucoadhesive assets of A. indica (Azadirachta indica) fruit mucilage by incorporating it into mucoadhesive microspheres with Acyclovir (AVR) as a model drug. The study was performed to check the impact of the mucilage proportion on particle size and swelling index. Nine batches of AVR mucoadhesive microspheres were made with varying proportions of Polyacrylic acid 934P and A. indica fruit mucilage (AIFM). A central composite design with design expert software to check the impact of dependent variables (A. indica mucilage and Polyacrylic acid 934 P levels) on particle size and swelling index as a response. As part of congeniality studies, the batches were examined for their physical constraints, AVR contents, and liberation. The particle size was found to be 35.2±0.3-48.1±0.6μm. In batch B-1, the particle was least sized compared to the larger size in B-5. The investigation found that the particle size and the swelling index depended on AIFM and Polyacrylic acid proportions. The research discovered that AVR was systematically released in a controlled manner and that the entrapment efficacy, mucoadhesion, drug content, and other constraints were found to be good. Acyclovir is capable of good stomach-specific drug delivery by Polyacrylic acid 934P and enhanced by A. indica fruit mucilage when prepared as mucoadhesive microspheres. Scanning electron microscopy reveals that the microspheres were spherical with a fairly smooth surface.